Comparative evaluation of commercially available AI-based cephalometric tracing programs - Nida Baig; Kabir Syed Gyasudeen; Tanmoy Bhattacharjee; Jahanzeb Chaudhry; Sabarinath Prasad (BMC, 2024)
Abstract Objectives Compare the accuracy and diagnostic concordance of three commercially available AI-based lateral cephalometric tracing software. Materials and methods Sixty-three lateral cephalometric radiographs were analyzed using semi-automatic (Dolphin Imaging Systems LLC) and AI-based software programs (WebCeph™, Cephio, and Ceppro DDH Inc.). Intra- and inter-observer reliability were assessed for human expert measurements, and repeated-measures one-way ANOVA was used to compare the AI and human expert measurements. The diagnostic performance was evaluated using sensitivity and specificity tests. Results Human expert reliability was excellent (ICC > 0.9) for most cephalometric parameters. Compared to human experts, significant differences were observed for all three AI-based cephalometric programs (WebCeph™ - 10 of 11, Cephio - 7 of 11, and Ceppro DDH Inc. - 7 of 11 cephalometric measurements). Variations exceeding two units were noted for most parameters, and differences in defining the sagittal and vertical skeletal patterns, dental, and soft tissue characteristics were observed. Conclusion All three AI-based tracing programs showed inaccuracies compared to human expert measurements and lacked reliability in measuring key cephalometric parameters. Clinicians should exercise caution when relying solely on AI-based analyses for orthodontic treatment planning and assessment.